The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1242/jcs.179655
|View full text |Cite
|
Sign up to set email alerts
|

The Rho GTPase Rif signals through IRTKS, Eps8 and WAVE2 to generate dorsal membrane ruffles and filopodia

Abstract: Rif induces dorsal filopodia but the signaling pathway responsible for this has not been identified. We show here that Rif interacts with the I-BAR family protein IRTKS (also known as BAIAP2L1) through its I-BAR domain. Rif also interacts with Pinkbar (also known as BAIAP2L2) in N1E-115 mouse neuroblastoma cells. IRTKS and Rif induce dorsal membrane ruffles and filopodia. Dominant-negative Rif inhibits the formation of IRTKS-induced morphological structures, and Rif activity is blocked in IRTKS-knockout (KO) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…IRSp53 and IRTKS are central modulators of actin dynamics downstream of the Rho family of small GTPases Cdc42, Rac1 and Rif281033. Consistent with their activities in mediating major physiological functions through interactions with multiple partners in different pathways, knockout models of Cdc42 and Rac are embryonic lethal at early gestation stages5051.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…IRSp53 and IRTKS are central modulators of actin dynamics downstream of the Rho family of small GTPases Cdc42, Rac1 and Rif281033. Consistent with their activities in mediating major physiological functions through interactions with multiple partners in different pathways, knockout models of Cdc42 and Rac are embryonic lethal at early gestation stages5051.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to IRSp53, IRTKS is phosphorylated upon insulin stimulation and its over-expression in cells leads to actin-rich membrane protrusions330. Notably, IRTKS lacks a Cdc42-interacting domain, but its I-BAR and SH3 domains have been shown to interact with several known IRSp53 partners such as Rac, Eps8 and Shank, suggesting the two proteins may overlap in mediating actin cytoskeletal remodelling induced by growth factor signalling30313233.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Tir has been shown to interact with the I-BAR domain of BAIAP2L1 to regulate actin pedestal formation (15). Likewise, it was also revealed that Rif colocalizes with BAIAP2L2 that is involved in edge ruffling at cell-cell contacts (16).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the I-BAR domains of both IRTKS and MIM are known to bind to small GTPase Rac1 [22,23], activation of which could lead to activation of Erk1/2. In addition to Rac1, IRTKS was recently reported to interact with small GTPase Rif by its I-BAR domain [24]. Hence, it is quite possible that IRTKS and MIM could bind to different small GTPases, which may influence profoundly their subsequent signaling under different cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could explain specific function of each I-BAR protein. For example, IRTKS induces dorsal membrane ruffles [24] and is associated with invadopodia in cancer cells and podosomes in osteoclasts [26]. In contrast, MIM induces filopodia-like protrusions when it is overexpressed [27].…”
Section: Discussionmentioning
confidence: 99%